Physiological characterization and electron microscopic investigation of cyanobacteria associated with wheat rhizosphere - Karthikeyan, N; Prasanna, R; Sood, A; Jaiswal, P; Nayak, S; Kaushik, B D (Folia microbiologica, 2009)
Physiological attributes of a set of cyanobacterial strains, isolated from the rhizosphere of wheat (var. HD 2687), identified as belonging to the genera Calothrix (n = 3), Westiellopsis (1), Hapalosiphon (2) and Nostoc (2), were axenized and evaluated. The concentrated culture filtrates of three cyanobacterial strains - C. ghosei, H. intricatus and Nostoc sp. were able to enhance germination percentage, radicle and coleoptile length in inhibition experiments with wheat seeds. Indole-3-acetic acid (IAA) production was recorded in light and dark (+0.5 % glucose) incubated cultures. Incubation in the presence of tryptophan significantly enhanced IAA production. Acetylene-reducing activity was higher in light incubated cultures of Nostoc sp. followed by C. ghosei, while in the dark, C. ghosei recorded highest values. TLC of the filtrates revealed the presence of several amino acids such as histidine, and auxin-like compounds. Co-culturing with selected strains recorded significant enhancement in plant chlorophyll. Root sections of wheat seedlings co-cultured with C. ghosei revealed the presence of short filaments inside the root hairs and cortical region. Such strains can be promising candidates for developing plant growth promoting associations for wheat crop, besides serving as model systems for understanding the metabolic interactions of cyanobacteria with host plant, such as wheat.
Keywords: kořeny rostlin; Cyanobacteria; Triticum; půdní mikrobiologie; Soil Microbiology; elektronová mikroskopie; sinice; pšenice; Microscopy, Electron; Indoleacetic Acids; kyseliny indoloctové; Plant Roots